2012
DOI: 10.1177/1090820x11430498
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Surgical Approach for Malar Alloplastic Augmentation

Abstract: The intranasal approach for alloplastic malar augmentation has shown good results for midface enhancement in the authors' hands. In this patient series, results showed excellent overall patient satisfaction and a very low (nearly 0%) complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The risk of vascular and nerve damage caused by subcutaneous dissection may be lower than that of subperiosteal dissection. Moreover, the intranasal approach probably decreases the risk of infection than the intraoral approach [8]. There were no infection cases in our patient population.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The risk of vascular and nerve damage caused by subcutaneous dissection may be lower than that of subperiosteal dissection. Moreover, the intranasal approach probably decreases the risk of infection than the intraoral approach [8]. There were no infection cases in our patient population.…”
Section: Discussionmentioning
confidence: 58%
“…Costal cartilage is also used to improve midface deficiency resulting in good long-term results [7]. The costal cartilage is carved into centimetre-level blocks and inserted into periosteal flap tunnels during rhinoplasty without sutures [8]. However, the long-standing direct pressure exerted by the blocks may damage the cranial bone causing complications, such as outer table skull erosion [9].…”
Section: Introductionmentioning
confidence: 99%
“…Peled et al [ 10 ] reported that silicone and Medpor have similar risks for infection. Silicone implants, when placed into appropriately sized pockets and held securely by surrounding tissues, are encapsulated by fibrous tissue with a minimal inflammatory response [ 11 12 ]. In our study, none of the patients experienced infection of the implanted pocket, nor did they experience capsular contracture around the silicone implant.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Intraoral, transpalpebral, transconjunctival, intranasal, and preauricular approaches have been described for the insertion of malar implants. 13 Plastic and Reconstructive Surgery • November 2022…”
mentioning
confidence: 99%